2018
DOI: 10.1038/s41598-018-26027-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Cellular retinoic acid-binding protein 2 as a potential target for rheumatoid arthritis synovial hyperplasia

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease including synovitis and synovial hyperplasia that contribute to joint destruction. Pivotal pathogenic mechanisms in this process are the dysregulated proliferation and apoptosis of fibroblast-like synoviocytes (FLS). Unfortunately, the mechanisms of FLS dysregulation are not completely elucidated. Here, we explored a new hypothesis based in the potent anti-proliferative and pro-apoptotic activity of retinoids in some types of cancer. Specifically, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…No previous study has analyzed the role of ATRA, or any other retinoid, in the RA FLS except for our previous work that was restricted to FLS proliferation and survival. FLSs' proliferation was insensitive to ATRA, whereas their resistance to apoptosis was exacerbated (Mosquera et al, 2018). The inhibitory effects of ATRA on FLS migration and invasion observed in the current study were in concordance with that found in cancerous and nonmalignant cells.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…No previous study has analyzed the role of ATRA, or any other retinoid, in the RA FLS except for our previous work that was restricted to FLS proliferation and survival. FLSs' proliferation was insensitive to ATRA, whereas their resistance to apoptosis was exacerbated (Mosquera et al, 2018). The inhibitory effects of ATRA on FLS migration and invasion observed in the current study were in concordance with that found in cancerous and nonmalignant cells.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, there is a growing interest in developing treatments aimed to revert the activated phenotype of RA FLS (Niedermeier et al, 2010). Recently, we found that a transporter of retinoids, cellular retinoic acid binding protein 2, is a candidate drug target of this type because cellular retinoic acid binding protein 2 suppression reverts RA FLS resistance to apoptosis (Mosquera et al, 2018). In the same study, we observed unconventional responses of RA FLS to the main biologic retinoid, all-trans retinoic acid.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations